Increased plasma lipopolysaccharide-binding protein and altered inflammatory mediators reveal a pro-inflammatory state in overweight women - Christine N. Metz; Michael Brines; Xiangying Xue; Prodyot K. Chatterjee; Robert P. Adelson; Jesse Roth; Kevin J. Tracey; Peter K. Gregersen; Valentin A. Pavlov (BMC Women's Health)
Abstract Background Chronic low-grade inflammation has been recognized as an underlying event linking obesity to diabetes and cardiovascular disease (CVD). However, inflammatory alterations in individuals and specifically women who are overweight remain understudied. Providing relevant insights is of substantial interest for women’s cardiovascular health. Methods We determined the levels of key circulating biomarkers of innate immune responses and inflammation, including lipopolysaccharide-binding protein (LBP), C-reactive protein (CRP), interleukin-6 (IL-6), leptin, and adiponectin in adult female subjects who were lean (n = 20) or overweight (n = 20) and had high cholesterol and/or high blood pressure - two important conventional risk factors for CVD. Results Plasma levels of LBP were significantly higher in the overweight group compared with the lean group (P = 0.017). The levels of CRP were also significantly higher in overweight subjects (P = 0.023), as were IL-6 (P = 0.016) and leptin (P = 0.004), pro-inflammatory mediators associated with cardiovascular risk. Levels of adiponectin, an adipokine with anti-inflammatory and anti-atherogenic functions, were significantly lower in the overweight group (P = 0.006). The leptin/adiponectin ratio, a preferential atherogenic marker was significantly increased in women who are overweight (P = 0.0007). LBP, CRP, leptin, IL-6, leptin, and adiponectin levels significantly correlated with BMI, but not with age and there was a significant correlation between LBP and IL-6 levels and LBP and CRP levels. Conclusions These results reveal the presence of a pro-inflammatory state in overweight women and are of interest for further studies with the goal for improved understanding of cardiovascular health risks in women.